Lessons from Tau-Deficient Mice. (6th June 2012) - Ke, Yazi D.; Suchowerska, Alexandra K.; van der Hoven, Julia; De Silva, Dineeka M.; Wu, Christopher W.; van Eersel, Janet; Ittner, Arne; Ittner, Lars M.
Abstract : Both Alzheimer's disease (AD) and frontotemporal dementia (FTD) are characterized by the deposition of hyperphosphorylated forms of the microtubule-associated protein tau in neurons and/or glia. This unifying pathology led to the umbrella term "tauopathies" for these conditions, also emphasizing the central role of tau in AD and FTD. Generation of transgenic mouse models expressing human tau in the brain has contributed to the understanding of the pathomechanistic role of tau in disease. To reveal the physiological functions of tau in vivo, several knockout mouse strains with deletion of the tau-encoding MAPT gene have been established over the past decade, using different gene targeting constructs. Surprisingly, when initially introduced tau knockout mice presented with no overt phenotype or malformations. The number of publications using tau knockout mice has recently markedly increased, and both behavioural changes and motor deficits have been identified in aged mice of certain strains. Moreover, tau knockout mice have been instrumental in identifying novel functions of tau, both in cultured neurons and in vivo . Importantly, tau knockout mice have significantly contributed to the understanding of the pathophysiological interplay between A β and tau in AD. Here, we review the literature that involves tau knockout mice to summarize what we have learned so far from depleting tau in vivo .